Epidemiology of Opportunistic Infections in HIV Infected Patients on Treatment in Accredited HIV Treatment Centers in Cameroon - Ornella Sybile D. Kouanfack, MD; Charles Kouanfack, MD, PhD; Serges Clotaire Billong, MD, PhD; Samuel N. Cumber, MPH, PhD; Claude N. Nkfusai, MSc; Fala Bede, MD, MPH; Emerson Wepngong, MD; Chombong Hubert, MSc; Georges N. K. Tsague Georges, MD, PhD; Madeleine N. Singwe, MD (Global Health and Education Projects, Inc., 2019)
Background: The African continent accounts for over 70% of people infected with Human Immunodeficiency Virus (HIV). The HIV sero-prevalence rate in Africa is estimated at 4.3%. In developed countries, such as France, pneumocystis is indicative of AIDS in 30% of patients; however, in Africa, pulmonary tuberculosis (TB) is the most-documented opportunistic infection (OI) and the leading cause of death in HIV-infected patients. In 2016, Cameroon had 32,000 new cases of OI and 29,000 deaths as a result of these infections. However, there is little existing data on the epidemiological profile of OIs in Cameroon, which is why we conducted this study in accredited HIV treatment centers and care/ treatment units in the two cities of Douala and Yaounde, Cameroon. Methods: This was a retrospective descriptive and analytical study carried out in 12 accredited HIV treatment centers in the cities of Yaoundé and Douala, Cameroon, over a period of seven months from October 2017 to April 2018. A stratified sampling method was used with three sampling levels: the city, type of health facility and size of active files. Ethical clearance and administrative authorization were obtained from the appropriate authorities and data were collected using a pre-tested survey form. The data collected were entered and analyzed with Epidata version 3.1 and SPSS version 3.5.3. Results: Out of a total of 1,617 HIV-infected patients sampled, 419 (25.9%) had at least one OI. Of these patients with an OI, 246 or 65% had a baseline CD4 count of <200/mm3. There was a significant relationship between the male gender and the onset of OI (OR = 1.47; p = 0.01). Age ? 50 years was associated with the occurrence of OI (OR = 2.57; p = 0.01). A CD4 count of <200/mm3 was also associated with the risk of developing an OI (OR = 3.12; p = <0.01). Conclusion and Global Health Implications: The prevalence of OI is high among people living with HIV. Shingles was the most common OI found followed by pulmonary tuberculosis. Male gender, age ? 50 years, and CD4 <200/mm3 were the most common factors associated with the occurrence of these OI. Key words: • Opportunistic infections • HIV/AIDS • Cameroon • AIDS treatment centers • ATC • UPEC • Tuberculosis • Shingles   Copyright © 2019 Kouanfack et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.